Association between KRAS mutations and the endoscopic and histopathological features of colorectal adenomatous polyps - Huyen, Le Thi Ngoc; Liem, Nguyen Thanh; Nhan, Kha Huu; Nhung, Thai Thi Hong; Sam, Nguyen Phan Hai; Phuc, La Vinh; Bao, Nguyen The; Duc, Tran Y; Loan, Luong Thi Thuy; Lan, Dang Nhu; Thien, Nguyen Tien; Loc, Huynh Van; et al. (Tạp chí Nghiên cứu Y học, 2026)
Colorectal adenomatous polyps are the principal premalignant lesions in colorectal carcinogenesis, and the combined evaluation of endoscopic features, histopathological characteristics, and molecular alterations such as KRAS mutations may help identify lesions with higher-risk features. This analytical cross-sectional study included 123 colorectal adenomatous polyps treated at Can Tho University of Medicine and Pharmacy Hospital from June 2024 to January 2026 to determine the prevalence of KRAS mutations and to assess the associations between KRAS mutation status and endoscopic and histopathological features. KRAS mutations were detected in 38.2% of polyps, predominantly at codon 12 (26.8%), followed by codon 13 (11.4%), no codon 61 mutation was identified. In univariable analyses, KRAS mutation status was associated with a nodular/lobulated surface, JNET type IIB–III classification, polyp size ≥10 mm, tubulovillous adenoma histology, and high-grade dysplasia. In multivariable logistic regression, only polyp size ≥10 mm (OR = 5.71; 95% CI: 2.08–15.67; p < 0.001) and high-grade dysplasia (OR = 6.81; 95% CI: 1.27–36.36; p = 0.025) remained significantly associated with KRAS mutation status. These findings suggest that KRAS mutations may be associated with more advanced features of colorectal adenomatous polyps, particularly larger size and high-grade dysplasia.